Evaluation of the Removal of Basic Blue 3 and Basic Yellow 28 Textile Dyes from Aqueous Media Using Persea americana 'Hass' Avocado Peel - Borklu Budak, Turkan (MDPI, 2026)
This study investigates the potential of Hass avocado peels as biosorbents for removing the cationic dyes BB3 and BY28 from aqueous solutions. The results demonstrate that agricultural waste can be effectively incorporated into sustainable, environmentally friendly wastewater treatment technologies. The adsorption parameters examined include adsorbent mass (0.1-1.1 g), dye concentration (5-50 mg/L), contact time (5-180 min), stirring speed (100-200 rpm), pH (4-10), and temperature (25-40 degrees C). UV-Vis spectrophotometric analyses show that the optimum conditions for BY28 removal are 0.3 g/50 mL adsorbent, 5 mg/L dye concentration, 30 min contact time, 200 rpm stirring speed, pH 7, and 40 degrees C, while those for BB3 are 1.1 g/50 mL adsorbent, 5 mg/L concentration, 45 min contact time, 150 rpm stirring speed, pH 7, and 40 degrees C. Under the optimized operating conditions, the maximum dye removal efficiencies were 88.24% for BY28 and 99.71% for BB3. This study demonstrates that agricultural waste can be converted into sustainable, reusable biosorbents for removing cationic dyes, thereby contributing to the development of environmentally friendly wastewater treatment technologies.
Keywords: adsorption; basic blue 3; basic yellow 28; wastewater; avocado peel; LOW-COST ADSORBENTS; EQUILIBRIUM; KINETICS; Biochemistry & Molecular Biology; Chemistry